Does firm performance impact top-level executive compensation in ESG companies? Evidence from India - Rath, Chetna; Deo, Malabika (Penerbit Universiti Kebangsaan Malaysia, 2021)
The huge disparity in the pay given to higher level executives in Indian companies has stirred a nation-wide debate regarding the viability of the pay-performance concept. On the other hand, the top-notch businesses claim to be good social performers by adhering to the rules, regulations and norms prevailing in the country concerning the welfare of the community encompassing it; broadly referred to as Environmental, Social and Governance (ESG) companies. The purpose of this paper is to examine and determine the link between firm performance (taken as independent variable) and compensation pay (considered as dependent variable) of such large as well as socially responsible companies. For sample of the firms, data has been collected from NSE Nifty 100 ESG Index and data for all other measures has been extracted from CMIE Prowess database. Panel regression results indicate that Return on Equity (ROE) has a significant negative impact while stock return of investors do have a significant positive impact on the compensation pay. In order to overcome the persistent underlying endogeneity issue, One-step System Generalised methods of moments (GMM) estimator has been employed. The overall findings indicate that accounting measure of firm performance exerts a significant impact on the compensation paid to the executives in ESG firms of India.